Silencing AT3 gene reduces the expression of pAmt, BCAT, Kas, and Acl genes involved in capsaicinoid biosynthesis in chili pepper fruits - M. L. Arce-Rodríguez; N. Ochoa-Alejo (Biologia Plantarum, 2015)
The effects of AT3-gene silencing on the expression of genes involved in capsaicinoid biosynthesis was investigated in chili pepper (Capsicum annuum L.) cv. Tampiqueño 74 fruits. Seeds were germinated and seedlings were grown in a greenhouse until they produced fruits. Capsaicinoids (capsaicin and dihydrocapsaicin) content and AT3 gene expression were determined in placenta tissue from fruits at 10, 20, 30, 40, 50, and 60 days post-anthesis (DPA). Capsaicin was more abundant than dihydrocapsaicin and both exhibited a similar accumulation pattern at different developmental stages starting at 20 DPA, reaching maximum values at 30-40 DPA before decreasing. The AT3 gene expression, as measured by quantitative RT-PCR, was positively correlated with capsaicinoid accumulation; AT3 transcripts were detected at 20 DPA, achieved a maximum at 30-40 DPA and then decreased. The Tampiqueño 74 seedlings were infected with Agrobacterium tumefaciens bearing a pTRV2-AT3 construct to induce virus-mediated silencing. Fruits were harvested at 40 DPA, and capsaicinoid content and AT3 gene expression were carried out in placenta tissue. A reduction of 81.1 % in AT3 expression and also in capsaicin (89.6 %) and dihydrocapsaicin (87.7 %) content was recorded in the AT3-gene silenced chili pepper plants. Furthermore, fruits from the AT3-silenced plants compared to the non-infected control plants showed a statistically significant reduction in the expression of genes involved in capsaicinoid biosynthesis [pAmt (89.4 %), BCAT (68.8 %), Kas (90.4 %) and Acl (58.6 %)]. These data indicate that AT3 silencing had a negative effect on the transcription of genes involved mainly in the branched-chain fatty acid pathway of capsaicinoid biosynthesis.